Adsorption of chlorophenolic compounds on activated clinoptilolite - Mustafa Uçar (Adsorption Science & Technology)
Nowadays, phenol and chlorophenols give rise to many organic pollutants. Concurrently, the occurring of phenolic compounds in aquatic ambit creates potential human health and environmental problems. There are a lot of technologies available for the treatment of organic pollutants. To remove phenol and chlorophenols, adsorption is a wastewater purification method. In this study, natural and activated clinoptilolite were carried out for the removal of phenol, ortho- chlorophenol, para -chlorophenol, and meta -chlorophenol. Activated clinoptilolite was prepared via acid activation and evaluated by means of Fourier transform infrared, scanning electron microscope, X-ray diffraction, X-ray fluorescence, and Brunauer–Emmett–Teller analysis. Phenol and chlorophenols have high adsorption rate, and equilibrium was reached in approximately 30 min. The maximum adsorptions of phenol, ortho- chlorophenol, meta -chlorophenol, and para -chlorophenols on the activated clinoptilolite were 6.7386, 8.6300, 9.5787, and 7.3758 mg g −1 , respectively. The affinity order was in the following order: m -CP > o-CP > p-CP > Ph. The adsorption of phenol and chlorophenols decreased after pH = 6.25. Using the thermodynamic data, Gibbs free energy of the activated clinoptilolite was evaluated. The effects of different conditions such as pH, adsorption time, and initial concentration were analyzed. The adsorption rates of phenol and chlorophenols were constituted to be the maximum at approximately pH 6.5. Desorption of phenol and chlorophenols was carried out using ethyl alcohol solution (30%, v/v). The adsorption isotherms of phenol and chlorophenols on activated clinoptilolite were evaluated. The equilibrium adsorption data were the best suited to Freundlich adsorption isotherm pattern.